Advances in the Exploration of Coordination Complexes of Vanadium in the Realm of Alzheimer’s Disease: A Mini Review - Jesús Antonio Cruz-Navarro; Luis Humberto Delgado-Rangel; Ricardo Malpica-Calderón; Arturo T. Sánchez-Mora; Hugo Ponce-Bolaños; Andrés Felipe González-Oñate; Jorge Alí-Torres; Raúl Colorado-Peralta; Daniel Canseco-Gonzalez; Viviana Reyes-Márquez; David Morales-Morales (Molecules, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline, memory loss and limited therapeutic options. Metal-based drugs have emerged as promising alternatives in the search for effective treatments, and vanadium coordination complexes have shown significant potential due to their neuroprotective and anti-aggregant properties. This review explores the advances in the development of vanadium-based metallodrugs for AD, focusing on their ability to modulate amyloid-beta (Aβ) aggregation, oxidative stress, and neuroinflammation. Recent in vitro and in vivo studies highlight the efficacy of oxovanadium (IV) and peroxovanadium (V) complexes in inhibiting Aβ fibril formation and reducing neuronal toxicity. Additionally, the interaction of vanadium complexes with key biological targets, such as peroxisome proliferator-activated receptor gamma (PPARγ) and protein-tyrosine phosphatase 1B (PTP1B), suggests a multifaceted therapeutic approach. While these findings underscore the potential of vanadium compounds as innovative treatments for AD, further research is needed to optimize their bioavailability, selectivity, and safety for clinical applications.